2010
DOI: 10.5142/jgr.2010.34.4.296
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Type II Peroxiredoxin Gene from Panax ginseng C. A. Meyer

Abstract: A peroxiredoxin cDNA (PgPrx) was isolated and characterized from the leaves of Panax ginseng. The cDNA is 716 nucleotides long and has an open reading frame of 489 base pairs with a deduced amino acid sequence of 162 residues. The calculated molecular mass of the mature protein is approximately 17.4 kDa with a predicted isoelectric point of 5.37. A GenBank BlastX search revealed that the deduced amino acid sequence of PgPrx shares a high degree homology with type II peroxiredoxin (Prx) proteins in other plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Its expression patterns indicated that is induced by ultraviolet irradiation, low temperature and salt stress. The induction of Prx in response to abiotic stimuli may suggest that Prx may protect the host against environmental stresses [60] . It looks like gene 42 affects gene 41 (HSP70T-2; ATP binding) and gene 7 (PSBS, (Nonphotochemical quenching), 16 (lipase, putative) and 38 (APX4 (Ascorbate peroxidase 4); peroxidase) and it is itself affected by 39 (GDCH (Glycine decarboxylase complex H)).…”
Section: Discussionmentioning
confidence: 99%
“…Its expression patterns indicated that is induced by ultraviolet irradiation, low temperature and salt stress. The induction of Prx in response to abiotic stimuli may suggest that Prx may protect the host against environmental stresses [60] . It looks like gene 42 affects gene 41 (HSP70T-2; ATP binding) and gene 7 (PSBS, (Nonphotochemical quenching), 16 (lipase, putative) and 38 (APX4 (Ascorbate peroxidase 4); peroxidase) and it is itself affected by 39 (GDCH (Glycine decarboxylase complex H)).…”
Section: Discussionmentioning
confidence: 99%
“…The total RNA was stored at À70 1C until use. Semi-quantitative RT reactions were conducted as reported previously (Kim et al, 2010c). The mRNA was quantified by realtime RT-PCR with SYBR Premix Ex Taq according to the manufacturer's instructions (Takara, Japan) using a real-time thermal cycler (Bio-Rad, USA) as reported previously (Khorolragchaa et al, 2010).…”
Section: Etoh/hcl-induced Gastritismentioning
confidence: 99%
“…Total RNA was stored at -70 °C until use. Analysis of mRNA was also performed using semiquantitative RT-PCR according to the manufacturer's instructions (Bioneer, Daejeon, Korea) as reported previously [21] . The results were expressed as the ratio of the optical density at 280 nm to the GAPDH mRNA concentration.…”
Section: Cell Culturementioning
confidence: 99%